Work and Leprosy: women in their pains, struggles and toils - Marcela Gonçalves; Michely Aline Rodrigues do Prado; Simone Santana da Silva; Karen da Silva Santos; Priscila Norié de Araujo; Cinira Magali Fortuna
ABSTRACT Objective: To analyze the interference of leprosy in women's life regarding work and daily life activities. Method: Exploratory qualitative study developed from semi-structured interviews and with the use of field diaries. The strategy of the organization of data was a thematic analysis of content and referential of the work process in health and gender. Results: The themes presented are: "The leprosy pains", "Changes with the disease and adaptation at work and activities" and "Being a woman with leprosy". On them, we present the aspects that changed in women's life from the leprosy, especially regarding work and daily activities. Beyond physical limitation, there are impacts on social relations and above all on formal work, there may even be dismission. Final considerations: In women affected by leprosy, work and daily activities are directly affected; this deepens the social difficulties and requires attention of health professionals.